Efforts to Improve Community Economy Through Utilization of Young Coconut Waste Into Cocofiber and Cocopeat on the Beach Sunur Pariaman Indonesia - Natsir, MHD; Solfema, Solfema; Dasa Putri, Lili; Tanwir, M (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This paper aims to describe the utilization of young coconut waste into coco fiber and coco peat on Sunur Beach Pariaman, Indonesia. This training activity is based on the lack of optimal waste management at Sunur Pariaman Beach. Even though it has good enough facilities, the awareness of keeping a clean environment has not been implemented well by the community. This causes visitors to feel uncomfortable with the trash everywhere and smashes the beautiful view of Sunur Beach. Young coconut waste is the most common waste found. The lack of trash cans and information boards that can educate people about clean living is one of the problems that must be resolved. Likewise, there is a lack of awareness of society's charms. The problems experienced by the community will surely hinder the process of developing Sunur Beach as a marine tourism location that is of interest to tourists. Based on this problem, training activities were carried out on the use of young coconut waste to make it economically valuable by turning it into coco fiber and coco peat. This activity seeks to contribute to waste management, especially young coconut waste, and educate the public about clean living by creating information boards and providing rubbish bins by utilizing the potential of local communities by providing training on processing young coconut waste into coco fiber and coco peat, education on clean living, and making information boards on cleaning living education, and throwing rubbish in its place. An active and participatory learning and KAP (Knowledge, Attitude, Practice) model approach is used to implement this program. The impact of this training is increasing public awareness of clean living, being able to utilize young coconut waste into cocopeat and coco fiber, improving families' economy, and supporting the realization of Sapta Pesona.